Low-dielectric-property composite material suitable for microwave silk degumming and preparation method of low-dielectric-property composite material
By using surface-modified mica, ultra-high molecular weight polyethylene chopped fibers and polyethylene resin composites as container materials for microwave silk degumming, the problems of high dielectric properties and seric adhesion of ceramic containers are solved, and a more efficient, safe and environmentally friendly silk degumming process is achieved.
Patent Information
- Application Number
- CN202411870615.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-18
AI Technical Summary
In the existing microwave silk degumming method, the high dielectric constant and dielectric loss of the ceramic container affect the degumming efficiency and energy consumption, and the high adhesion of the seric glue leads to adhesion to the container wall, affecting the degumming effect.
Low dielectric composite materials prepared from surface-modified mica, ultra-high molecular weight polyethylene chopped fibers and polyethylene resin composites are used as container materials for microwave silk degumming. The composite material has low dielectric constant, low dielectric loss and good thermal conductivity, avoids overheating of the container and reduces the adhesion of the sericin.
It improves the efficiency and safety of the microwave silk degumming process, reduces energy consumption, and optimizes the mechanical properties and molding processability of the composite material.
Smart Images

Figure CN119752006A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, and in particular to a method for preparing a composite material with low dielectric properties suitable for microwave silk degumming. Background Art
[0002] Silk is a protein fiber with a pleasing luster, soft feel and excellent moisture absorption and breathability. It has always been used as a high-end textile raw material in the textile field. Silk is mainly composed of fibroin and sericin. Among them, fibroin accounts for about 75% of the total content, and sericin accounts for about 25%. Due to the great difference in the structural properties of fibroin and sericin, when the silk fiber (raw silk) reeled from silk cocoons is woven into fabrics or other silk products, the presence of sericin will affect the luster, feel and texture of the textile products and the subsequent processing quality. Therefore, in the textile industry, most of the sericin in raw silk or raw silk grey cloth must be removed. This process is the degumming of silk or fabric (also known as refining), that is, the separation of fibroin fiber and sericin protein.
[0003] Fibroin is a fibrous protein that is insoluble in water, and sericin is a globular protein that is soluble in hot water. The general degumming method is based on the different water solubility of the two. Chemical reagents containing acids, alkalis, soaps, synthetic detergents or enzymes are used to dissolve sericin in the degumming bath to remove the sericin. Conventional chemical reagent degumming not only consumes a lot of energy, but also discharges a large amount of wastewater containing sericin and chemicals, which puts great pressure on the environment. In addition, as a by-product of raw silk degumming, sericin has good moisturizing ability, biological activity and pharmacological effects. Recovering sericin from the silk degumming process can not only reduce water pollution, but also provide valuable raw materials for industries such as food, medicine and cosmetics. However, the sericin produced in the existing degumming (refining) process contains a large amount of chemical additives used in degumming, and can generally only be treated as waste, which not only increases the environmental load, but also wastes sericin, a valuable natural protein resource.
[0004] To this end, workers in the silk industry have been committed to developing clean and environmentally friendly degumming processes and have made some research progress. For example, electrolytic water degumming, infrared heating degumming, CO2 supercritical fluid degumming, calcium hydroxide degumming, etc. have appeared in recent years. However, some of these degumming methods are still uneconomical or the direct recovery of sericin is more complicated. Therefore, it is necessary to continuously explore new treatment processes in order to truly realize the green processing of silk degumming.
[0005] At present, there have been studies on the use of microwaves for silk degumming. Microwaves are a clean, high-frequency electromagnetic wave energy source with the characteristics of high efficiency, uniform heating and high penetration. However, since the degumming temperature is around 100°C. Although ceramic containers are relatively heat-resistant, their dielectric constant and dielectric loss are relatively large, and due to the high adhesion of sericin, it is easy to adhere to the container wall. When the dielectric constant and dielectric loss of microwave containers are large, the efficiency and energy consumption of silk degumming are affected, and the adhesion of sericin further affects the degumming efficiency and effect. Although polymer materials with lower polarity have lower dielectric constants and surfaces that are not easy to adhere to sericin, their thermal conductivity is often small. Since the container is located in a fixed microwave cavity, local overheating is prone to occur during continuous microwave degumming, which brings safety problems. Affecting the practical application of microwave silk degumming. Summary of the invention
[0006] In view of the problems in the prior art, the present invention provides a low dielectric composite material suitable for microwave silk degumming and a preparation method thereof. The present invention uses surface modified mica and ultra-high molecular weight polyethylene chopped fibers as reinforcing materials and a mixture of low-density linear polyethylene and high-density polyethylene as a matrix to prepare a low dielectric composite material. The low dielectric composite material has low surface energy, low dielectric constant and low dielectric loss, and has good thermal conductivity, which can avoid the occurrence of container overheating, and is suitable for use in microwave silk degumming.
[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions: A low-dielectric composite material suitable for microwave silk degumming, wherein the low-dielectric composite material is composited by surface-modified mica, ultra-high molecular weight polyethylene chopped fibers, and polyethylene resin; the polyethylene resin is composed of linear low-density polyethylene and high-density polyethylene.
[0008] Polyethylene resin has ultra-low dielectric constant and low dielectric loss due to its unique structure without polar groups in its molecules. Among them, high-density polyethylene has good toughness, chemical corrosion resistance and good fluidity, and can be processed by various molding methods such as extrusion, injection molding, and compression molding, and the use temperature is relatively high, while linear low-density polyethylene resin has a lower dielectric constant. The two can be mixed in a certain proportion to give full play to their advantages.
[0009] However, due to the low thermal conductivity of polyethylene resin, adding mica can improve the thermal conductivity and reduce the heat accumulation during microwave heating. At the same time, the addition of ultra-high molecular weight polyethylene chopped fibers can make the mica better dispersed in the resin matrix and increase the mechanical properties of the composite material.
[0010] Preferably, in the polyethylene resin, the mass ratio of linear low-density polyethylene to high-density polyethylene is 1:1-3.
[0011] Preferably, the mass ratio of the surface modified mica, ultra-high molecular weight polyethylene chopped fibers and polyethylene resin is 1: 0.5 to 1: 4 to 10. In the present invention, if the proportion of polyethylene resin is too low, the dielectric constant is affected, and if the proportion is too high, the thermal conductivity is affected.
[0012] Preferably, the preparation method of the surface-modified mica comprises the following steps: placing the mica in isopropanol, subjecting the mica to a microwave-ultrasonic combined treatment at 50-60°C for 30-90 min, then adding a surface treatment agent of 0.5%-1% by mass of the mica, subjecting the mica to an ultrasonic treatment at 50-60°C for 3-5 h, and then filtering and drying to obtain the surface-modified mica; the surface treatment agent is one or more of hexadecyltrimethylammonium bromide and fatty amine salts.
[0013] Preferably, the mass volume ratio of mica to isopropanol is 1 g:15-25 mL.
[0014] Preferably, the length of the ultra-high molecular weight polyethylene chopped fibers is 2.5-4.5 mm. Ultra-high molecular weight polyethylene chopped fibers are formed by cutting ultra-high molecular weight polyethylene long fibers in the process of preparing low dielectric properties composite materials. The chopped fibers can effectively disperse mica, increase the mechanical properties of the composite materials, and increase the use temperature of the composite materials, and are easy to form; if the chopped fibers are too short, the mechanical reinforcement effect is not good, and if they are too long, the processing performance will be affected, and the surface of the molded product will be easily fuzzy.
[0015] Preferably, the low dielectric composite material is tested by the resonant cavity method at a frequency of 1M, and the dielectric constant is 2.00-2.15, the dielectric loss is ≤0.0007, and the thermal conductivity is 0.6-0.9 W / (m 2 ·k).
[0016] The present invention provides a method for preparing a composite material with low dielectric properties suitable for microwave silk degumming, comprising the following steps: S1: mixing linear low-density polyethylene and high-density polyethylene in a mixer to obtain polyethylene resin; S2: heating and melting the polyethylene resin to obtain a resin melt A; injecting the resin melt A and the surface-modified mica into a heating container, stirring, to obtain a mica-containing resin melt B, injecting the resin melt B into an impregnation tank with a heating device; S3: passing ultra-high molecular weight polyethylene long fibers with a twist of 200-600 T / m through an impregnation tank containing a resin melt B to obtain ultra-high molecular weight polyethylene long fibers with the resin melt B adhered to the surface, and after curing in air, cutting into short pieces with a length of 2.5-4.5 mm to obtain short fiber prepreg; S4: subjecting the chopped fiber prepreg to molding to obtain the low dielectric performance composite material.
[0017] In step S3, ultra-high molecular weight polyethylene long fibers with a twist of 200-600 T / m are used. The main reason is that the surface energy of ultra-high molecular weight polyethylene fibers is low, and twisting is performed to increase the surface roughness to facilitate the adhesion of the resin melt containing mica. If the twist is too low, the number of coils per unit length is small, which affects the adhesion effect. If the twist is too high, the fiber is prone to produce excessive centrifugal force due to untwisting during cutting, thereby causing the adhered resin to fall off.
[0018] Preferably, in step S3, the ultra-high molecular weight polyethylene long fibers are passed through an impregnation tank containing a resin melt at a speed of 0.5 to 15 m / min.
[0019] Preferably, in step S4, the chopped fiber prepreg is molded by a twin-screw extrusion process or a hot pressing process.
[0020] The beneficial effects of the present invention are: 1. The low dielectric composite material product prepared by the present invention is suitable for the container of silk microwave degumming. On the one hand, it can reduce the energy loss in the silk microwave degumming process based on the low dielectric constant and low dielectric loss of low-density linear polyethylene and high-density polyethylene mixture, and the low surface energy of polyethylene can reduce the adhesion of sericin. On the other hand, surface-modified mica is introduced into the matrix, which can not only increase the thermal conductivity of the composite material, but also improve the deformation temperature of the matrix, and reduce the overheating phenomenon of the container in the silk microwave degumming process. In addition, ultra-high molecular weight polyethylene fiber is introduced, and the mechanical properties of the composite material can be increased without affecting the dielectric constant, and the molecular structure of the ultra-high molecular weight polyethylene fiber is consistent with the molecular structure of the matrix polyethylene, and good interface compatibility is arranged.
[0021] 2. The present invention uses twisted ultra-high molecular weight polyethylene fibers to increase the adhesion of the mica particle-containing resin to the fibers. The method for preparing chopped fiber prepreg by adhering long fibers to the mica particle-containing resin can increase the dispersibility of mica particles and ultra-high molecular weight polyethylene chopped fibers in the matrix and the molding processability of the composite material, thereby optimizing the performance of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 The figure is a schematic diagram of the preparation process of the chopped fiber prepreg of the present invention. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Embodiment 1: A low dielectric composite material suitable for microwave silk degumming is composited with surface modified mica, ultra-high molecular weight polyethylene chopped fibers, and polyethylene resin; the polyethylene resin is composed of linear low-density polyethylene and high-density polyethylene. In the polyethylene resin, the mass ratio of linear low-density polyethylene to high-density polyethylene is 1:1; the mass ratio of surface modified mica, ultra-high molecular weight polyethylene chopped fibers and polyethylene resin is 1:0.5:10.
[0026] This embodiment is applicable to the preparation method of a composite material with low dielectric properties for microwave silk degumming, comprising the following steps: S1: 10 g of mica was placed in a container containing 200 mL of isopropanol, the container was covered, and then placed in an ultrasonic microwave combined reactor, and subjected to microwave-ultrasonic combined treatment at 60°C for 30 min, and then 1% of the mass of mica, hexadecyltrimethylammonium bromide, was added, and ultrasonic treatment was performed at 60°C for 4 h, and then the surface-modified mica was obtained by filtration and drying; S2: 50 g of linear low-density polyethylene and 50 g of high-density polyethylene are mixed in a mixer to obtain a polyethylene resin; S3: 100 g of polyethylene resin is placed in a heating container and heated to melt to obtain a resin melt A; 100 g of the resin melt A and 10 g of surface-modified mica are simultaneously and slowly injected into a heating container with a stirring function, and after stirring, a mica-containing resin melt B is obtained, and the resin melt B is injected into an impregnation tank with a heating device; S4: passing the ultra-high molecular weight polyethylene long fiber with a twist of 400 T / m through an impregnation tank containing a resin melt B at a speed of 15 m / min, and curing in air to obtain an ultra-high molecular weight polyethylene fiber with the resin melt B adhered to the surface, and cutting it into a length of about 3 mm to obtain a short fiber prepreg; S5: The short-cut fiber prepreg is molded by a hot pressing process (temperature of 132° C., pressure of 5 MPa, time of 30 min) to obtain the low dielectric performance composite material.
[0027] Embodiment 2: A low dielectric composite material suitable for microwave silk degumming is composited with surface modified mica, ultra-high molecular weight polyethylene chopped fibers, and polyethylene resin; the polyethylene resin is composed of linear low-density polyethylene and high-density polyethylene. In the polyethylene resin, the mass ratio of linear low-density polyethylene to high-density polyethylene is 1:1.5; the mass ratio of surface modified mica, ultra-high molecular weight polyethylene chopped fibers and polyethylene resin is 1:0.8:5.
[0028] This embodiment is applicable to the preparation method of a composite material with low dielectric properties for microwave silk degumming, comprising the following steps: S1: 10 g of mica was placed in a container containing 150 mL of isopropanol, the container was covered, and then placed in a microwave-ultrasonic combined reactor, and microwave-ultrasonic combined treatment was performed at 50° C. for 90 min, and then 0.5% of the mass of mica, hexadecyltrimethylammonium bromide was added, and ultrasonic treatment was performed at 50° C. for 5 h, and then the surface-modified mica was obtained by filtering and drying; S2: 20 g of linear low-density polyethylene and 30 g of high-density polyethylene are mixed in a mixer to obtain a polyethylene resin; S3: 50 g of polyethylene resin is placed in a heating container and heated to melt to obtain a resin melt A; 50 g of the resin melt A and 10 g of surface-modified mica are slowly injected into a heating container with a stirring function at the same time, and after stirring, a mica-containing resin melt B is obtained, and the resin melt B is injected into an impregnation tank with a heating device; S4: passing the ultra-high molecular weight polyethylene long fibers with a twist of 600 T / m through an impregnation tank containing a resin melt B at a speed of 5 m / min, and curing in air to obtain ultra-high molecular weight polyethylene long fibers with the resin melt B adhered to the surface, and cutting them into a length of about 3 mm to obtain short-cut fiber prepreg; S5: The short-cut fiber prepreg is molded by a hot pressing process (temperature of 132° C., pressure of 5 MPa, time of 30 min) to obtain the low dielectric performance composite material.
[0029] Embodiment 3: A low dielectric composite material suitable for microwave silk degumming is composited with surface modified mica, ultra-high molecular weight polyethylene chopped fibers, and polyethylene resin; the polyethylene resin is composed of linear low-density polyethylene and high-density polyethylene. In the polyethylene resin, the mass ratio of linear low-density polyethylene to high-density polyethylene is 1:3; the mass ratio of the surface modified mica, ultra-high molecular weight polyethylene chopped fibers and polyethylene resin is 1:1:4.
[0030] This embodiment is applicable to the preparation method of a composite material with low dielectric properties for microwave silk degumming, comprising the following steps: S1: 10 g of mica was placed in a container containing 250 mL of isopropanol, the container was covered, and then placed in an ultrasonic microwave combined reactor, and subjected to microwave-ultrasonic combined treatment at 60°C for 60 min, and then 1% of the mass of mica, hexadecyltrimethylammonium bromide, was added, and ultrasonic treatment was performed at 50°C for 5 h, and then the surface-modified mica was obtained by filtration and drying; S2: 10 g of linear low-density polyethylene and 30 g of high-density polyethylene are mixed in a mixer to obtain a polyethylene resin; S3: 40 g of polyethylene resin A is placed in a heating container and heated to melt to obtain resin melt A; 40 g of resin melt A and 10 g of surface-modified mica are slowly injected into a heating container with a stirring function at the same time, and after stirring, a mica-containing resin melt B is obtained, and the resin melt B is injected into an impregnation tank with a heating device; S4: passing an ultra-high molecular weight polyethylene long fiber with a twist of 200 T / m through an impregnation tank containing a resin melt at a speed of 0.5 m / min, and curing in air to obtain an ultra-high molecular weight polyethylene long fiber with the resin melt B adhered to the surface, and cutting it into a length of about 4 mm to obtain a short fiber prepreg; S5: The short-cut fiber prepreg is molded by a hot pressing process (temperature of 132° C., pressure of 5 MPa, and time of 30 min) to obtain the low dielectric performance composite material.
[0031] Performance Test: The dielectric constant and dielectric loss of the low dielectric composite material prepared by the method in Examples 1 to 3 were tested at a frequency of 1 M, and the thermal conductivity was tested.
[0032] Table 1 Performance test results data Dielectric constant Dielectric loss <![CDATA[Thermal conductivity / W / (m 2 ·k)]]> Example 1 2.00 0.0006 0.60 Example 2 2.11 0.0007 0.85 Example 3 2.15 0.0007 0.90 As shown in Table 1, the low dielectric composite materials prepared by the methods in Examples 1 to 3 all have dielectric constants and low dielectric losses, and have excellent thermal conductivity. It can be seen that the low dielectric composite material products obtained by the composite molding method of the present invention can be used to make containers for silk microwave degumming.
[0033] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A low dielectric composite material suitable for microwave silk degumming, characterized in that: The low dielectric performance composite material is composited by surface modified mica, ultra-high molecular weight polyethylene chopped fibers and polyethylene resin; the polyethylene resin is composed of linear low-density polyethylene and high-density polyethylene.
2. The low dielectric composite material suitable for microwave silk degumming according to claim 1, characterized in that: In the polyethylene resin, the mass ratio of linear low-density polyethylene to high-density polyethylene is 1:1-3; the mass ratio of the surface-modified mica, ultra-high molecular weight polyethylene chopped fibers to the polyethylene resin is 1:0.5-1:4-10.
3. The low dielectric composite material suitable for microwave silk degumming according to claim 1, characterized in that: The preparation method of the surface modified mica comprises the following steps: The mica is placed in isopropanol, subjected to microwave-ultrasonic combined treatment at 50-60° C. for 30-90 min, and then a surface treatment agent of 0.5%-1% by mass of the mica is added, subjected to ultrasonic treatment at 50-60° C. for 3-5 h, and then filtered and dried to obtain surface-modified mica; the surface treatment agent is one or more of hexadecyltrimethylammonium bromide and fatty amine salt.
4. The low dielectric composite material suitable for microwave silk degumming according to claim 3, characterized in that: The mass volume ratio of the mica and isopropanol is 1 g: 15-25 mL.
5. The low dielectric composite material suitable for microwave silk degumming according to claim 1, characterized in that: The length of the ultra-high molecular weight polyethylene chopped fibers is 2.5-4.5 mm.
6. The low dielectric composite material suitable for microwave silk degumming according to claim 1, characterized in that: The low dielectric composite material is tested by the resonant cavity method under the condition of 1M frequency, and the dielectric constant is 2.00-2.15, the dielectric loss is ≤0.0007, and the thermal conductivity is 0.6-0.9 W / (m 2 ·k).
7. A method for preparing a low dielectric composite material suitable for microwave silk degumming as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: S1: mixing linear low-density polyethylene and high-density polyethylene in a mixer to obtain polyethylene resin; S2: heating and melting the polyethylene resin to obtain a resin melt A; injecting the resin melt A and the surface-modified mica into a heating container, stirring, to obtain a mica-containing resin melt B, injecting the resin melt B into an impregnation tank with a heating device; S3: passing ultra-high molecular weight polyethylene long fibers with a twist of 200-600 T / m through an impregnation tank containing a resin melt B to obtain ultra-high molecular weight polyethylene long fibers with the resin melt B adhering to the surface, and after curing in air, cutting into short pieces with a length of 2.5-4.5 mm to obtain short fiber prepreg; S4: subjecting the chopped fiber prepreg to molding to obtain the low dielectric performance composite material.
8. The preparation method according to claim 7, characterized in that: In step S3, the ultra-high molecular weight polyethylene long fiber is passed through an impregnation tank containing a resin melt at a speed of 0.5-15 m / min.
9. The preparation method according to claim 7, characterized in that: In step S4, the chopped fiber prepreg is molded by a twin-screw extrusion process or a hot pressing process.
Citation Information
Patent Citations
High-strength supermicroporous fiber-reinforced composite material and preparation method thereof
CN103146047A
Prepreg, forming method thereof and wave-transmitting material
CN104513456A
Low dielectric thermoplastic resin based fiber compound material and application thereof
CN106957528A
Preparation method and equipment of novel ultralow dielectric resin material
CN115418086A
Manufacture of long fiber reinforced polyolefin resin composition
JP1998230517A